Constant motion/force transmission analysis and synthesis of a class of translational parallel mechanisms. (February 2017) - Zhao, Yanzhi; Wang, Jinglei; Cao, Yachao; Liang, Bowen; Zhao, Tieshi
Abstract: Motion/force transmission is one of the most important issues and the foundation of analysis and optimal design in the field of parallel mechanisms. It reflects the capacity that each limb in a parallel mechanism transmits its driving force to the moving platform and also the output capacity of the moving platform under definite input of the limb. Several performance indices were proposed to measure motion/force transmission. However, they are instantaneous values varying with different poses. In this paper, a criterion for constant power transmission and the excellent motion/force transmission occurring within a class of translational parallel mechanisms in different poses is proposed based on screw theory. To obtain the translational parallel mechanisms with constant and excellent motion/force transmission, a host of configurations are synthesized based on constraint screw theory when the criterion is met. The criterion proposed in this paper is expected to be applied for the translational parallel mechanisms to analyzing motion/force transmission and optimizing the design. Highlights: Criterion for constant power transmission and the excellent motion/force transmission occurring within a class of translational parallel mechanisms is proposed. A host of configurations of the translational parallel mechanisms which meet the criterion are synthesized. The motion/force transmission performance of two translational mechanisms 3-CRU and 3-PRRU are analysed. The "original" input power is introduced and the angle between the axial directions of the TWS and MTS which exactly reflects the capacity of the "original" input to output transmission is presented.